PENILAIAN PORTOFOLIO OPTIMAL PADA SEKTOR PERBANKAN INDEKS LQ45 - Nevia Fitriyani (Cakrawala Management Business Journal, 2020)
The purpose of this study is to assess which stocks are eligible for optimal portofolio formation and calculate the portion of funds for each stock forming the portofolio, and determine the optimal return of portofolio expectations with the risks faced by investors. This study uses a single index method. The population in this study were 44 banking sector companies that went public on the Indonesia Stock Exchange. The sample was selected by using purposive sampling technique in the banking sector stocks that entered consecutively into the LQ45 Index for the period January 2015-December 2019. The results of this study showed that out of 5 stocks sample, there were 3 stocks that were eligible for optimal portfolio, namely Bank Central Asia Tbk. (BBCA) with a proportion of funds 75.18%, Bank Tabungan Negara (Persero) Tbk. (BBTN) with a proportion of funds of 17.08%, and Bank Rakyat Indonesia (Persero) Tbk. (BBRI) with a proportion of funds of 7.74%. With an optimal portfolio expected return of 0.39% and a risk that must be faced by 0.43%.